2013
DOI: 10.1590/s0034-75902013000400005
|View full text |Cite
|
Sign up to set email alerts
|

Influência da conexão política na diversificação dos grupos empresariais brasileiros

Abstract: ResUMoArgumentamos que a abordagem teórica baseada na economia política fornece explicações alternativas para o fenômeno da diversificação dos grupos empresariais no Brasil em relação à abordagem baseada na economia dos custos de transação. Utilizamos doações empresariais às campanhas eleitorais como proxy de conexões políticas para testar a abordagem da economia política frente à abordagem mainstream de custos de transação. Estimamos um modelo de regressão em painel com efeito fixo em uma amostra de 760 obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
(3 reference statements)
0
8
0
12
Order By: Relevance
“…Camilo et al (2012) studied political connections and their eff ects on company performance using three proxies: donations to political campaigns, the hiring of members with political backgrounds to compose executive boards or boards of directors, and board interlocking activities. Costa et al (2013) verifi ed the infl uence of political connections in the diversifi cation of Brazilian business groups. Macedo et al (2015) examined the issue from an analyst perspective and whether they would be likely to maintain their portfolios of investments in companies that have explicit political connections.…”
Section: Board Of Director Interlockingmentioning
confidence: 98%
“…Camilo et al (2012) studied political connections and their eff ects on company performance using three proxies: donations to political campaigns, the hiring of members with political backgrounds to compose executive boards or boards of directors, and board interlocking activities. Costa et al (2013) verifi ed the infl uence of political connections in the diversifi cation of Brazilian business groups. Macedo et al (2015) examined the issue from an analyst perspective and whether they would be likely to maintain their portfolios of investments in companies that have explicit political connections.…”
Section: Board Of Director Interlockingmentioning
confidence: 98%
“…Por exemplo, o BNDES ofereceu linhas de crédito para investimentos de longo prazo e representou o principal instrumento fomentador da formação de grandes conglomerados de empresas brasileiras voltados para a internacionalização (GUEDES, 2006;CERVO;BUENO, 2011). MARCON, 2013). Garcia (2012) afirma que, por trás de uma grande empresa há sempre um Estado forte, que organiza o campo político e jurídico para que a organização possa operar e crescer.…”
Section: Referencial Teóricounclassified
“…In India, they belong to 4.2 sectors, and, in the Philippines, 3.5 sectors (Khanna & Yafeh, 2007). Additionally, a recent study showed that, in Brazil, diversification of family business groups is at around 4 sectors per group (Costa, Bandeira-de-Mello, & Marcon, 2013). Concerning vertical integration, there are groups that belong to different and correlated industries.…”
Section: Family Business Groupsmentioning
confidence: 99%
“…Valor Grandes Groups is an annual publication available on the newspaper Valor Econômico, Brazil's leading periodical on business and finance. Information gathered from Valor Grandes Grupos has previously been used in other academic studies (Aldrighi & Postali, 2010;Costa et al, 2013;Xavier, Marcon, & Bandeira-de-Mello, 2013). Data showed that, among the top 200 Brazilian business groups, only 38 run foreign operations.…”
Section: Datamentioning
confidence: 99%